Evaluation of top-down cracking potential for asphalt pavements with 4.75 mm nominal maximum aggregate size mixture layer using full-scale field tests and finite element analysis. Issue 5 (4th July 2018) - Chun, Sanghyun; Kim, Kukjoo; Greene, James; Choubane, Bouzid
Abstract : This study primarily focused on evaluating top-down cracking resistance for pavement structures with 4.75 mm nominal maximum aggregate size asphalt mixtures (i.e. SP-4.75) that will help determine more effective application of these mixes for layered flexible pavement system. Crack evaluation and pavement surface response measurements were conducted using full-scale field test sections. In addition, a three-dimensional (3-D) viscoelastic finite-element (FE) pavement model was developed to further validate the results of field tests using analytical solution. The results indicated that the pavement structure with SP-4.75 mixture at the top becomes more prone to top-down cracking when a thin layer with unmodified asphalt binder is applied. It was found that both layer thickness and binder type are key parameters to control top-down cracking potential. Also, the comparative observations between analytical and experimental results confirm that the FE model developed was able to provide accurate, reliable, and realistic prediction for change in pavement surface strain responses due to different conditions of SP-4.75 layer application. It was concluded that adequate thickness and binder type should be considered for proper application of SP-4.75 mixture as a surface course of layered flexible pavement system to effectively resist top-down cracking.